2012
DOI: 10.1371/journal.pntd.0001642
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Native Lipid Moiety of Echinococcus granulosus Antigen B

Abstract: Antigen B (EgAgB) is the most abundant and immunogenic antigen produced by the larval stage (metacestode) of Echinococcus granulosus. It is a lipoprotein, the structure and function of which have not been completely elucidated. EgAgB apolipoprotein components have been well characterised; they share homology with a group of hydrophobic ligand binding proteins (HLBPs) present exclusively in cestode organisms, and consist of different isoforms of 8-kDa proteins encoded by a polymorphic multigene family comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
23

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(87 citation statements)
references
References 54 publications
4
60
0
23
Order By: Relevance
“…Tapeworms, like flukes, lack the ability to synthesize cholesterol de novo, and until now there has been no conclusive research on the biosynthesis of estrogens, progesterone, and androgens in cestodes (17). Metabolic and transcriptomic studies have demonstrated that sterol synthesis in E. granulosus is interrupted at the level of farnesyl or nerol-idol pyrophosphate, that the cholesterol derives from the host, and that for signaling actions, the host sterols may be modified by the parasite (38). But it is highly likely that if Echinococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Tapeworms, like flukes, lack the ability to synthesize cholesterol de novo, and until now there has been no conclusive research on the biosynthesis of estrogens, progesterone, and androgens in cestodes (17). Metabolic and transcriptomic studies have demonstrated that sterol synthesis in E. granulosus is interrupted at the level of farnesyl or nerol-idol pyrophosphate, that the cholesterol derives from the host, and that for signaling actions, the host sterols may be modified by the parasite (38). But it is highly likely that if Echinococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…2-DGE and MS analysis was performed as described previously [38] but using 150 μg (protein) of the AgB-enriched fraction (QS f ) for the electrofocusing step in order to detect poorly represented subunits. Briefly, the first dimension was performed with commercially available IPG-strips (7 cm, linear 3–10, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…AgB total lipids were analysed using Ld f (between 0.25 and 0.5 mg of protein) following the methodology that we have already described [38]. Qualitative analysis of lipid classes was performed by HPTLC using double development for neutral and polar lipids as described previously [38], but lipid bands were visualised under iodine vapour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reason, using fatty materials as energy sources is expensive for tapeworms (Obal et al,2012).…”
Section: Fatty Acid Analysis In the Intestinal Tapewormmentioning
confidence: 99%